2017
DOI: 10.1016/j.watres.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating UV-C LED disinfection performance and investigating potential dual-wavelength synergy

Abstract: A dual-wavelength UV-C LED unit, emitting at peaks of 260 nm, 280 nm, and the combination of 260|280 nm together was evaluated for its inactivation efficacy and energy efficiency at disinfecting Escherichia coli, MS2 coliphage, human adenovirus type 2 (HAdV2), and Bacillus pumilus spores, compared to conventional low-pressure and medium-pressure UV mercury vapor lamps. The dual-wavelength unit was also used to measure potential synergistic effects of multiple wavelengths on bacterial and viral inactivation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
166
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 267 publications
(183 citation statements)
references
References 37 publications
10
166
0
7
Order By: Relevance
“…In earlier UV-LED studies more than 3 Log 10 -reductions of coliphages φX174 and T7 were achieved with doses of 6.4-20 mWs/cm 2 at wavelengths of 255-285 nm [18,24]. Coliphages Qβ and MS2 were more resistant and they required above 40 mWs/cm 2 to reach 1-3 Log 10 -reductions [13,16,18,21,23,24]. Bowker et al [18] compared the wavelengths of 255 and 275 nm with coliphages T7 and MS2 and found rather similar inactivation rates at both wavelengths.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In earlier UV-LED studies more than 3 Log 10 -reductions of coliphages φX174 and T7 were achieved with doses of 6.4-20 mWs/cm 2 at wavelengths of 255-285 nm [18,24]. Coliphages Qβ and MS2 were more resistant and they required above 40 mWs/cm 2 to reach 1-3 Log 10 -reductions [13,16,18,21,23,24]. Bowker et al [18] compared the wavelengths of 255 and 275 nm with coliphages T7 and MS2 and found rather similar inactivation rates at both wavelengths.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to a single wavelength, simultaneous treatment with multiple wavelengths of UV-C and UV-A have yielded higher reductions of fecal enterococci and total and fecal coliforms in wastewater and in pure cultures [40,41] and Vibrio parahaemolyticus in pure culture [42]. On the other hand, the UV-LEDs at wavelengths 260 nm and 280 nm irradiated separately or simultaneously yielded statistically similar reductions in E. coli, Bacillus pumilus spores, MS2, or adenovirus when the UV-doses were the same [13]. More studies are obviously needed on the effect of different wavelength combinations on viruses and other resistant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations